MENELAAH TAFSIR AL-QUR'AN MELALUI LENSA ANALISIS WACANA KRITIS - Annisa, Ayu; Idrus Alkaf; Halimatussa’diyah (Al-Dirayah, 2024)
This research aims to explore the interpretation of the Qur'an through the Critical Discourse Analysis (CDA) approach. The Qur'an, as a sacred text in Islam, plays a crucial role in providing spiritual guidance and laws for Muslims. However, traditional understandings of the Qur'an often limit the expression of holistic and relevant meanings in the context of modern times. In an effort to attain a deeper and contextual understanding, this research proposes the use of CDA as an interpretative lens. CDA offers a critical and reflective framework for analyzing texts, revealing power structures, ideologies, and conflicts contained within. Through this approach, the research aims to open new interpretative spaces for the Qur'an, enabling a more comprehensive and relevant understanding of its messages. The research methodology involves analyzing selected Qur'anic texts using the CDA framework, focusing on the revelation of power structures, conflicts, and ideologies within the texts. It is expected that the results of this research will significantly contribute to the development of Islamic religious thought and strengthen the relevance of the Qur'an in the context of modern life.